Indurated soil nodules: A vestige of ancient agricultural practices?. Issue 6 (4th August 2022) - Giosa, Alain; Delbey, Thomas; Menbrivès, Clément; Rasmussen, Kaare L.; Elliott, Michelle; Petit, Christophe
Abstract: The identification of controlled fires in ancient agricultural systems is important for understanding how past societies managed the landscape. Although the use of fire in agriculture is documented in recent historical records, and combustion markers can persist in soils over a long time scale, this is a complex issue because combustion traits in general are ubiquitous. Archaeopedological surveys undertaken in an ancient forest in Burgundy (France) have led to the recovery of several red indurated nodules scattered in the soils. Gallo‐Roman housing structures and parcels were recognized using light detection and ranging mapping, stimulating questions about the understanding of the nature of these nodules. Elemental and structural analyses by  X‐ray fluorescence and X‐ray diffraction (XRD) confirmed the local origin of these features by comparing their composition with on‐site sediments, and thermoluminescence dating placed the samples in the Medieval period. The results cast light on the nature of the nodules and how they can be related to controlled fires used in agricultural practices. Even though questions remain about which processes lead to the formation of the nodules, the firing temperature estimated via XRD analysis seems to be in agreement with that used in the "paring‐and‐burning" technique. The present study provides new information about medieval agriculture practices from the 10th to the 12th centuries CE and shows how past societies managed the opening and maintenance of agricultural fields using natural resources and "archaeological" remains from the antique period.